Quantitative Assessment of Intestinal Injury Using a Novel In Vivo, Near-Infrared Imaging Technique - Todd W. Costantini; Brian P. Eliceiri; Carrie Y. Peterson; William H. Loomis; James G. Putnam; Andrew Baird; Paul Wolf; Vishal Bansal; Raul Coimbra (Molecular Imaging)
Intestinal injury owing to inflammation, severe trauma, and burn is a leading cause of morbidity and mortality. Currently, animal models employed to study the intestinal response to injury and inflammation depend on outdated methods of analysis. Given that these classic intestinal assays are lethal to the experimental animal, there is no ability to study the gut response to injury in the same animal over time. We postulated that by developing an in vivo assay to image intestinal injury using fluorescent dye, it could complement other expensive, time-consuming, and semiquantitative classic means of detecting intestinal injury. We describe a novel in vivo, noninvasive method to image intestinal injury using a charge-coupled device (CCD) camera that allows for serial visual and quantitative analysis of intestinal injury. Our results correlate with traditional, time–consuming, semiquantitative assays of intestinal injury, now allowing the noninvasive, nonlethal assessment of injury over time.